(3OQGSGJ fXQjI h JWHjbjI eJYebIs - (3YHO GdMj(B, (3eQYjs; (3WGMhf eMeO YHO GdMejO(B, s ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3GdHGH GdGhd (B: (3bjGS GdJcdaI dGZQV GdJNWjW eY GdJQcjR Ydi GdaJQI GdbUjQI j JNWjW hJfXje hQbGHI GdYedjGJ GdLGQjI JNWjW GdGgOGa , aj GdYdGbI Hjf GdJcdaI hGdMLe hGdQHM , aj eONd GdJcGdja GdeHGTQI hGSJNOGeGJg , aj GdJcdaI dGZQGV JNWjW GdGSJeQGQ aj GdYedjI GdGfJGLjI aj GdeOi GdWhjd GdHGH GdKGfj aj bjGS GdJcdaI dGZQGV GdQbGHI ebOeI aj fXGe GdQbGHI Ydi GdJcGdja fXGe GdeMGSHI GdeSDhdjI , OhQ GdeYGjjQ hGdehGRfGJ aj GdQbGHI Ydi GdJcGdja , JMdjd GfMQGaGJ GdCQHGM heSHHGJgG , JMdjd hJaSjQ GfMQGaGJ GdehGO GdeHGTQI hGdYed GdeHGTQ JMdjd GfMQGaGJ GdJcGdja GdGVGajI GdUfGYjI , aj GdJcGdja GdeYjGQjI dGZQGV JMOjO JcdaI GdGfJGL ,aj GdJcGdja GdeYjGQjI hGdGSGdjH GdGMUGFjIs
Keywords: (3GdJNWjWs; (3GdQbGHI GdeGdjIs; (3eMGSHI GdJcGdjas